2021
DOI: 10.1002/bab.2281
|View full text |Cite
|
Sign up to set email alerts
|

The genus Simplicillium and Emericellopsis: A review of phytochemistry and pharmacology

Abstract: The demand for novel and improved medicine from biological sources to cater to the biopharmaceutical sector has increased significantly in recent years. Among the vast and miscellaneous microbial diversity, fungi provide a prolific source of structurally unique and biologically active secondary metabolites. Natural products obtained from fungi have reformed the era of biomedicine, providing effective drugs that have diverse healing potential. In this review, we focus on the isolation, chemical structure, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The 2D NMR data analysis (Figure S121) and the MS 2 data (Figures S53 and S61 S9). Considering the 2D NMR data and MS 2 (Figures S69 and S77) fragment ion at m/z 1708 (b 18 ), 7 and 8 were assigned as the 19-residue analogues of 5 and 6 with an extra Ala 19 residue at the C-terminus, respectively. S8) for 9 showed similarities with those of 5, except for the loss of a phenolic hydroxyl proton from the Tyr residue, and the chemical shift migration of some signals around the second to the fifth residues in 9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D NMR data analysis (Figure S121) and the MS 2 data (Figures S53 and S61 S9). Considering the 2D NMR data and MS 2 (Figures S69 and S77) fragment ion at m/z 1708 (b 18 ), 7 and 8 were assigned as the 19-residue analogues of 5 and 6 with an extra Ala 19 residue at the C-terminus, respectively. S8) for 9 showed similarities with those of 5, except for the loss of a phenolic hydroxyl proton from the Tyr residue, and the chemical shift migration of some signals around the second to the fifth residues in 9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10−14 These secondary structures can affect the ion channels formation and endow peptaibiotics with membrane permeabilizing properties, which are related to their biological functions, 15,16 such as antibiotic and neuroactive activities. Plenty of natural peptaibiotics were biosynthesized by nonribosomal peptide synthetase pathway and discovered from fungi, 17 especially the species of genera Trichoderma, 18 Emericellopsis, 19 Acremonium, 20 Gliocladium, 21 Hypocrea, 22 and Cephalosporium. 23 In agriculture, some of these fungi are biocontrol strains, so the peptaibiotics derived from them are usually applied in controlling plant diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 Only a few reports are available on the isolation of anti-MRSA compounds from Emericellopsis sp. [20][21][22] and it is yet to be thoroughly investigated for the discovery of novel compounds. Moreover, isolation of anti-MRSA compounds from Indian marine environments has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…are ubiquitous in the marine environment and can exist under extreme conditions such as temperature, pressure, salinity, and pH 19 . Only a few reports are available on the isolation of anti‐MRSA compounds from Emericellopsis sp 20–22 . and it is yet to be thoroughly investigated for the discovery of novel compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that species of Emericellopsis are important sources of bioactive metabolites, such as peptaibols with antibacterial and antifungal activities [8,9]. The Norine database [10], which is dedicated to non-ribosomal peptide synthases (NRPS), includes some of these compounds: the antiamoebins I-XI from E. salmosynnemata and E. synnematicola, the bergofungins A-D from E. donezkii, the emerimicins II-IV from E. microspora and E. minima, the heptaibin from Emericellopsis sp.…”
Section: Introductionmentioning
confidence: 99%